DECOLONIZATION OF KNOWLEDGE IN ISLAMIC BOARDING SCHOOL: AN ANALYSIS OF THE EPISTEMOLOGIES OF BAYANI, BURHANI, AND IRFANI AS COUNTER-HEGEMONY - Fathur Rosi Dennismas A; Ainul Yakin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study aims to examine the potential of Islamic boarding schools (pesantren) as spaces for decolonizing knowledge through the epistemological approaches of bayani, burhani, and irfani. These three Islamic epistemologies, as proposed by Muhammad Abid al-Jabiri, offer a unique framework of rationality and serve as an important basis for the formation of an Islamic scientific paradigm. Using a library study method and a hermeneutical analysis approach, this study explores the relevance of these three epistemologies in the context of Islamic boarding school education as a space for resistance to the hegemony of Western knowledge. The results of the study indicate that Islamic boarding schools can act as centers of counter-hegemony through the integration of textual bayani, rational burhani, and spiritual irfani. The synergy of these three epistemologies strengthens the epistemic autonomy of Islam and opens up opportunities for the development of a decolonial educational model characterized by ethical and contextual characteristics.